2012
DOI: 10.1073/pnas.1206286109
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein disrupts stress signaling by inhibiting polo-like kinase Cdc5/Plk2

Abstract: Parkinson disease (PD) results from the slow, progressive loss of dopaminergic neurons in the substantia nigra. Alterations in α-synuclein (aSyn), such as mutations or multiplications of the gene, are thought to trigger this degeneration. Here, we show that aSyn disrupts mitogen-activated protein kinase (MAPK)-controlled stress signaling in yeast and human cells, which results in inefficient cell protective responses and cell death. aSyn is a substrate of the yeast (and human) polo-like kinase Cdc5 (Plk2), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 29 publications
1
35
1
Order By: Relevance
“…Contrary to our observation, their data showed that deletion of the 11 first amino acids of ␣-syn is sufficient to alter the interaction and the phosphorylation of ␣-syn by CDC5, the yeast ortholog of human PLK2 (21). This apparent discrepancy could be due to the fact that although orthologs, the protein structures of CDC5 and PLK2 are different (only 30% homology; UniProt), which may implicate distinct protein regions and conformations for the interaction with ␣-syn.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Contrary to our observation, their data showed that deletion of the 11 first amino acids of ␣-syn is sufficient to alter the interaction and the phosphorylation of ␣-syn by CDC5, the yeast ortholog of human PLK2 (21). This apparent discrepancy could be due to the fact that although orthologs, the protein structures of CDC5 and PLK2 are different (only 30% homology; UniProt), which may implicate distinct protein regions and conformations for the interaction with ␣-syn.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous work by Wang et al (21) studied ␣-syn and PLK2 interaction in yeast cells. Contrary to our observation, their data showed that deletion of the 11 first amino acids of ␣-syn is sufficient to alter the interaction and the phosphorylation of ␣-syn by CDC5, the yeast ortholog of human PLK2 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of yeast cell lysates, SDS/PAGE, and Western blot analysis was carried out as described previously (31). Protein concentrations were determined using a bicinchoninic acid assay (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…␣Syn can be phosphorylated in yeast by endogenous kinases (55). Several kinase families are reported to phosphorylate ␣Syn at Ser-129 in higher eukaryotes (19 -22, 27, 28, 56 -58).…”
Section: Protective Function Of Sumo Requires Direct Modification Of mentioning
confidence: 99%